Investigation of the Influences of the bandwidths in Hysteresis current controller on single phase inverters - Hazrati, Tina; Hahn, Ingo (2024 International Symposium on Power Electronics, Electrical Drives, Automation and Motion, SPEEDAM 2024, 2024)
At the present time, due to climate change and global warming, reducing the energy consumption of electrical drives is a necessity. According to the advanced technological improvement of power electronics devices, the hysteresis current control techniques (HCC) has been widely used for small systems because of their simple implementation and excellent dynamic performance. Moreover, owing to their simplicity, insensitivity to load parameters' variations, fast dynamic response and inherent maximum current limiting characteristics, hysteresis current control is a rather popular one among different current control techniques. This paper investigates the influence of the hysteresis bandwidth of a two-level single-band controller with predefined target current amplitude and DC-voltage on the total dissipated energy and the current's THD of a single-phase system. The simulation model of the simple passive inductive-resistive network and the power inverter with the idealized switches (here: SiC MOSFETs) have been implemented in Scilab 6.0.2 simulation environment. The obtained results suggest not to use only a narrow hysteresis bandwidth but also lower current amplitudes and lower DC voltages depending on the application.
CRIS-Team Scopus Importer:2024-08-30
Keywords: DC-voltage; hysteresis bandwidth; hysteresis current controller (HCC); total harmonic distortion (THD)